Use of time series models to forecast the evolution of corrosion pit in steel rebars - Xu Yidong (Functional Materials, 2016)
This paper presents the time series method to forecast the evolution of pitting depth in corroded reinforcing steel bars. Basic time series analysis models are introduced, and the method for establishing the autoregressive integrated moving average (ARIMA) model is described through an example. Based on ARIMA model, the pitting depth in reinforcing steel bars under two different corrosion environments is predicted. The results show that ARIMA model can describe the variation tendency of pitting depth in corroded reinforcing steel bars quantitatively. The predicted values and the observed ones are in good conformity.